Neurological involvement in COVID-19 - Dhungana, Isha; Shrestha, Prabin (Nepal Journal of Neuroscience, 2021)
Corona Virus Disease 2019 (COVID-19) pandemic has been currently going on around the world. The causative virus, Severe Acute Respiratory Syndrome Corona Virus type 2 (SARS-Cov-2), has been detected in various human body fluids including cerebrospinal fluid. Neurological involvement is one of the important aspects of COVID-19. Though many things in this regard have been published earlier, all the information are scattered and no article has tried to include all the information. Therefore, the main purpose of this article is to summarize all the relevant information about neurological involvement of COVID-19 in a single article. More than one hundred recently published or pre-print articles have been collected and analyzed in this review. While searching the literatures, keywords such as COVID-19, SARS-CoV-2, encephalitis, stroke, intracranial hemorrhage, neurological manifestations, complications etc. were entered. Pubmed, Medscape etc. were used as a source of information. Neurological involvement in COVID-19 has been emerging as a matter of interest and further investigation for many who are involved in its management. Though many literatures and reports have explained various neurological aspects of COVID-19, many queries are still unanswered and needs further investigation. Spectrum of neurological involvement, exact mode and basic pathophysiology of central nervous system involvement, possibility of detection of virus in cerebrospinal fluid etc. are yet to be answered which are discussed and addressed in this review. Based on our analysis, we have discussed on various aspects of neurological involvement in COVID-19 in this review.